STUDENTS’ PREFERENCES OF THE RESEARCH PROPOSAL WRITING FEEDBACK - Lindawaty Bunga Djaya Kusuma; Wisma Yunita; Mei Hardiah (Universitas Muhammadiyah Metro, 2022)
Students' feedback preferences are essential in the research proposal writing process. This research aims to reveal the students' preferences toward the supervisor has written feedback and the types of written feedback provided by the supervisors in the students' research proposal in terms of the error correction feedback and the comment feedback. This research employed a mixed-method design. There were 39 samples chosen purposively to gain the quantitative data and 16 documents chosen from five random students to gain the qualitative data. Based on the data analysis, the type of error correction feedback and comment feedback preferred by the students respectively are the direct error correction feedback with the score of 155 (38,46%) and the directive comment feedback with 293 (22,37%). Besides, the type of error correction feedback and comment feedback provided by the supervisors respectively are the direct error correction feedback with 79 (51,97%) scores and the referential comment feedback with the scores of 206 (63,00%). This study implies that various feedback should address the students' preferences and learning styles since the outputs are their academic writing achievement.